Xanthogranulomatous Pancreatitis Accompanied by Xanthogranulomatous Cholecystitis: A Case Report and Literature Review. Issue 7 (August 2021) - Imokawa, Tomoki; Ito, Kyoji; Takemura, Nobuyuki; Inagaki, Fuyuki; Mihara, Fuminori; Kokudo, Norihiro
Abstract: Xanthogranulomatous pancreatitis (XGP) is extremely rare, with only 31 cases reported in the English literature to date. We reviewed previously reported 17 articles about XGP and report an additional case of XGP. This is the first case of XGP with xanthogranulomatous cholecystitis accompanied by intraductal papillary mucinous carcinoma (IPMC) in an 80-year-old woman. She was referred to our hospital with jaundice and general malaise and was found to have a cystic mass at the pancreatic head and a solid mass at the pancreatic tail, with dilation of both the main pancreatic duct and biliary tract noted on computed tomography. Diagnosis of IPMC at the pancreatic head with neuroendocrine tumor at the pancreatic tail was made, and the patient underwent subtotal stomach-preserving pancreatoduodenectomy with enucleation of the mass at the tail. Pathological examination revealed IPMC with xanthogranulomatous changes around the IPMC and at the pancreatic tail and gallbladder. Xanthogranulomatous pancreatitis could be induced by inflammatory reaction due to obstruction of the pancreatic duct and biliary tract by mucin produced in the IPMC. It is sometimes difficult to preoperatively differentiate XGP from malignant pancreatic tumors, such as pancreatic carcinoma or neuroendocrine tumor, using imaging studies.